Lama, Kedalaman dan Frekuensi Penyelaman terhadap Kejadian Barotrauma Telinga pada Nelayan Penyelam Tradisional - Utari Yunie Atrie; Linda Widiastuti; Liza Wati; Yusnaini Siagian; Soni Hendra Sitindaon (Jurnal Keperawatan Silampari, 2023)
This study aims to analyze the effect of length, depth, and conversion frequency on the incidence of ear barotrauma in traditional fishermen in Malang, Meeting Village, and Bintan Regency, Riau Archipelago. The method used in this quantitative research is analytic observational with a case-control research design. The results showed that there was a relationship between length, depth, and frequency of isolation on the incidence of ear barotrauma in traditional healing in Malang, which was demonstrated through the results of the Chi-Square test analysis on various factors, namely p = 0.048 (time of rescue), p = 0.001 ( healing depth) and p=0.001 (healing frequency). The multiple logistic regression test results obtained p-value = 0.00 (p <0.05). In conclusion, duration, depth, and frequency of diving affect health problems, especially ear barotrauma in traditional healing fishermen. Of the various adaptation factors, depth is the factor that most influence ear barotrauma incidence in traditional diving fishermen. Keywords: Ear Barotrauma, Frequency of healing, Depth of healing, Long Dive, Fisherman Traditional Diving